Resepsi Khalayak Terhadap Pemberitaan Kasus Antasari Azhar Dalam Portal Berita Online - Ramdani Soalohon; Hedi Pudjo Santoso, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
Online media is electronic-technology through internet network providing information and entertainment speedily, affordable and easily to access by public. In every online media, we may discover a number of news portals that provide various informations speedily and easily in our daily life. The statement from Antasari Azhar, stating that he was criminalised by his political opponents, caused special attraction from online media to cover it as news continuously. Therefore, the objective of this study is to reveal how the reception from the public toward the case covering Antasari Azhar in online news portals is. This study is qualitative descriptive research by using reception analysis as the approach. It applies encoding-decoding model from Stuart Hall’s to explain the process of encoding-decoding news from online news portals. The results of this study shows that; different background found between informants and media, as well all different educational background of each other, tended to create different assumption. On the informant, who possess similar cultural knowledge to the media and have middle to high educational background, tended to assume the texts offered by media (dominant reading), the public received the fact covered by online news portal based on preferred reading (the meaning offered by media). They gave stigma that Antasari Azhar was not involved in act of Nazrudin Zulkarnaen murder. While Informant, who possess middle to low and middle to high educational background, whose social status and cultural experience are different from the media, tended to read the news in negotiative way (negotiated reading), they were neutral since some texts coming from similar media, but some are assummed differently, so that the stigma given from Antasari Azhar case was negotiative. While the informants, who have middle to high educational background, tended to read the news radically (oppositional reading), their stigma was the news reported by online news portals were not neutral, and the informants assumed that they did not really know whether Nasrudin Zulkarnaen was murdered by Antasari Azhar, or Antasari Azhar did murder Nasrudin Zulkarnaen. This study is open to be examined from different points of view and methods and becomes the basis of further research, especially about the political issue in online news portal and active audience, so it may enrich the study about audience/public reception.